Unearthing Linguistic and Historical Treasures: Analysis of Traces of Pro-to-Austronesian in Ancient Malay Inscriptions from Hindu-Buddhist Antiq-uities in Padang Lawas, North Sumatra - Napitupulu, Merlin Helentina; Qhodari, Qhodari; Venroy, Venroy (Jurnal Ilmu Pendidikan dan Humaniora, 2023)
This research delves into the linguistic and historical dimensions of Padang Lawas, a region in North Sumatra, Indonesia, by conducting an in-depth analysis of ancient Malay inscriptions originating from Hindu-Buddhist antiquities. The central objective of the study is to identify traces of Proto-Austronesian, the ancestral language of the Austronesian language family, within these inscriptions and to place them within their broader historical and cultural context. The linguistic analysis begins with the identification of linguistic features, including vocabulary, phonological elements, and syntactical structures, that echo Proto-Austronesian characteristics. By comparing these features with reconstructed Proto-Austronesian and related languages, the research aims to shed light on the linguistic evolution of the Malay language and its historical connections. The historical context is illuminated by examining the inscriptions within the framework of the Hindu-Buddhist period in Padang Lawas. This entails a thorough exploration of religious practices, trade networks, and societal structures that defined the region during this era. Additionally, the inscriptions' references to both Hindu and Buddhist deities reveal the syncretism of beliefs that characterized the cultural landscape. Regional variations in the inscriptions highlight the diversity of cultures and dialects within Padang Lawas, enriching our understanding of linguistic and cultural interactions. Ethical considerations have guided the research, emphasizing the preservation of cultural heritage, responsible research, and collaboration with local communities and authorities. The findings of this research have profound implications. They contribute to the fields of linguistics, history, and archaeology, offering fresh insights into language evolution, historical context, and the interplay of cultures in Southeast Asia. Furthermore, they advocate for the preservation of cultural heritage, responsible research practices, and interdisciplinary collaboration as models for future investigations.